Letters to a young writer : some practical and philosophical advice - McCann, Colum, 1965- (New York : Random House, 2017)
"From the bestselling author of the National Book Award winner Let the Great World Spin comes a lesson in how to be a writer--and so much more than that. Intriguing and inspirational, this book is a call to look outward rather than inward. McCann asks his readers to constantly push the boundaries of experience, to see empathy and wonder in the stories we craft and hear. A paean to the power of language, both by argument and by example, Letters to a Young Writer is fierce and honest in its testament to the bruises delivered by writing as both a profession and a calling. It charges aspiring writers to learn the rules and even break them. These fifty-two essays are ultimately a profound challenge to a new generation to bring truth and light to a dark world through their art. Praise for the fiction of Colum McCann Let the Great World Spin Winner of the National Book Award "One of the most electric, profound novels I have read in years."--Jonathan Mahler, The New York Times Book Review "There's so much passion and humor and pure life force on every page that you'll find yourself giddy, dizzy, overwhelmed."--Dave Eggers TransAtlantic Longlisted for the Man Booker Prize and shortlisted for the International IMPAC Dublin Literary Award "Reminiscent of the finest work of Michael Ondaatje and Michael Cunningham."--O: The Oprah Magazine "Another sweeping, beautifully constructed tapestry of life. Reading McCann is a rare joy."--The Seattle Times Thirteen Ways of Looking A New York Times Notable Book of the Year "The irreducible mystery of human experience ties this small collection together, and in each of these stories McCann explores that theme in strikingly effective ways."--The Washington Post "Extraordinary. incandescent."--Chicago Tribune"--
"Drawing on the lessons learned throughout a distinguished writing career and nearly 20 years as a teacher of creative writing, McCann delivers a collection of essays that combines practical advice, creative inspiration, and a profound call to arms for a new generation of writers to bring truth and light to a dark world through their art. Addressing subjects such as "The Terror of the White Page," "Embrace the Critics," and "If You're Done, You've Just Begun," this collection is a testament to the bruises of writing as profession and as calling, and a paean to the power of language"--
Introduction: The Unsayable Ecstasies -- Letter to a Young Writer --There Are No Rules -- Your First Line -- Don't Write What You Know -- The Terror of the White Page -- No Ideas Without Music -- A Hero of Consciousness -- Out from the Dust: Creating Characters -- Shaping the Truth -- Carry a Notebook -- Be a Camera -- Fuhgheddaboudit: Writing Dialogue -- Read Aloud -- Who What Where When How and Why -- Seeking Structure -- What Matters: Language and Plot -- Punctuation: It's Not Just a Throwaway Thing (Comma) -- Research: Google Isn't Deep Enough -- No Rust on Your Sentences Please -- The Habit of Hoping -- There are No Literary Olympics -- How Old is the Young Writer? -- Don't Be a Dick -- Then Again, Don't Be Too Nice -- Fail, Fail, Fail -- Read, Read, Read -- Rejoyce -- Writing is Entertainment -- Take a Break -- Who's Your Ideal Reader? -- How to Get an Agent -- What if I Don't Get an Agent? -- Finding the Right Editor -- Bringing (Your Own) Fresh Eyes to Your Stories -- Throw It All Away -- Allow the Reader's Intelligence -- Success -- If You're Done, You've Only Just Begun -- Blurbs (or the Art of Literary Porn) -- A Secret Hearing -- Where Should I Write? -- To MFA or Not to MFA? -- Should I Read While I'm Writing? -- Smash that Mirror -- The Dark Dogs of the Mind -- Write Yourself a Credo -- The Bus Theory -- Why Tell Stories -- Embrace the Critics -- Be Exhausted When You Finish -- Your Last Line -- Letter to a Young Writer, Redux.
"National Book Award-winning author of Let the Great World Spin"--Dust Jacket.
Keywords: Creative writing; Authorship; Authorship -- Vocational guidance; LANGUAGE ARTS & DISCIPLINES / Composition & Creative Writing; REFERENCE / Writing Skills; SELF-HELP / Personal Growth / General